Tracing technoscapes the production of Bronze Age wall paintings in the Eastern Mediterranean - Becker, Johannes 1983-; Jungfleisch, Johannes; Rüden, Constance von (Sidestone Press, 2018)
Colorful surface treatments form an integral element of vernacular and élite architecture of ancient societies. This is also true for the various regions of the Eastern Mediterranean in the 2nd millennium B.C.E., where elaborate wall paintings furnished temples, tombs, palatial buildings, and in general more elaborate houses. From a present-day perspective, these rich images provide invaluable insights into past realities as well as interconnections between different visual systems. However, beyond stunning images, the materiality of wall paintings implicates a whole range of specific technical choices and gestures executed during the artistic process. The bodies of knowledge immanent in the practice of plaster and pigment preparation, in the application of paint and in the conception and execution of compositions allow us to compare the wall painting corpora of the Eastern Mediterranean on a technical level and to trace differences and similarities in a cross-cultural perspective. Evolved from an interdisciplinary workshop held at the 10th ICAANE in Vienna, this volume provides insights into the various technical approaches and underlying bodies of knowledge in the different wall painting traditions of the Eastern Mediterranean and West Asia and throws light on the way and extent of their possible interwovenness. Moreover, it seeks to overcome regional as well as disciplinary isolation of technical studies by bringing together authors of different scientific backgrounds ranging between Conservational Studies, Archaeometry, Prehistory, Egyptology, as well as Western Asiatic and Classical Archaeology. In doing so, the book permits an interdisciplinary perspective on this field of study. This book is equally intended for archaeologists, art historians, conservators and the interested layperson and hopes to stimulate more research in this direction in future
Keywords: Wandmalerei; Maltechnik; Bronzezeit; Mittelmeer -- Ost; Konferenzschrift -- 2016 -- Wien